2019
DOI: 10.4252/wjsc.v11.i9.705
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hepatic differentiation in the subpopulation of human amniotic stem cells under 3D multicellular microenvironment

Abstract: BACKGROUNDTo solve the problem of liver transplantation donor insufficiency, an alternative cell transplantation therapy was investigated. We focused on amniotic epithelial cells (AECs) as a cell source because, unlike induced pluripotent stem cells, they are cost-effective and non-tumorigenic. The utilization of AECs in regenerative medicine, however, is in its infancy. A general profile for AECs has not been comprehensively analyzed. Moreover, no hepatic differentiation protocol for AECs has yet been establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…One of the major obstacles of translating hAESCs into the clinic is the heterogeneity in primary amnion epithelial cell population and discrepancies in their cell surface profiling (Centurione et al, 2018) that can be primarily attributed to isolation protocols, gestational age, passage number, and epithelial to mesenchymal transition (Ghamari et al, 2020). However, hAESCs isolated from the adherent subpopulations of passaged primary cells, and cultured in 3D environment may successfully overcome these limitations and may express a higher level of stemness properties (Ferdousi et al, 2019;Furuya et al, 2019). Additionally, protocol for immortalized human amniotic epithelial cells with high expressions of stem cell markers has been reported (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major obstacles of translating hAESCs into the clinic is the heterogeneity in primary amnion epithelial cell population and discrepancies in their cell surface profiling (Centurione et al, 2018) that can be primarily attributed to isolation protocols, gestational age, passage number, and epithelial to mesenchymal transition (Ghamari et al, 2020). However, hAESCs isolated from the adherent subpopulations of passaged primary cells, and cultured in 3D environment may successfully overcome these limitations and may express a higher level of stemness properties (Ferdousi et al, 2019;Furuya et al, 2019). Additionally, protocol for immortalized human amniotic epithelial cells with high expressions of stem cell markers has been reported (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported hepatic differentiation potentials of hAECs using multistep proliferation and differentiation protocols involving several combinations of growth factors and cytokines (Marongiu et al, 2011;Lin et al, 2015;Liu et al, 2018;Maymó et al, 2018). In our previous study, we have reported that the hAECs isolated from the adherent subpopulations of passaged primary cells have widely expressed stemness markers (Furuya et al, 2019). We have also shown that hAECs cultured in a 3D microenvironment as spheroids have highly expressed the stemness-related genes compared to their 2D counterpart (Ferdousi et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…In our previous studies, a detailed methodology of hAEC extraction, culture, and 3D spheroid formation have been documented (Ferdousi et al, 2019;Furuya et al, 2019). Briefly, hAECs were extracted from the term placenta.…”
Section: Extraction Of Amnion Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations